Theo. A. Bingham papers - Bingham, Theo. A. (Theodore Alfred), 1858-1934.
Newspaper clippings, photographs, and other papers relating to official functions at the White House; the assassination of William McKinley (1901); the visit of Heinrich, Prince of Prussia (1902); and the unveiling of a statue of Jean-Baptiste-Donatien de Vimeur, comte de Rochambeau, in Washington, D.C. (1902).
Library of Congress Prints and Photographs Division.
Army officer. Between 1897 and 1903 Bingham was in charge of public buildings and grounds in Washington, D.C., under the U.S. Army Corps of Engineers Office of Public Buildings and Grounds.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Heinrich, -- Prince of Prussia, -- 1862-1929.; McKinley, William, -- 1843-1901 -- Assassination; Rochambeau, Jean-Baptiste-Donatien de Vimeur, -- comte de, -- 1725-1807 -- Statues; White House (Washington, D.C.); Statues -- Washington (D.C.); Washington (D.C.) -- Social life and customs; Army officers